The Development of the Modern Labor Market under the Conditions of an Innovative Economy (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the adaptation of the labor market to new conditions during the formation of an innovative economy, the changing requirements for personnel qualifications, and the impact of the digital transformation process on the workforce composition. Based on theoretical and practical analysis, the paper studies the current state of Uzbekistan’s labor market using statistical data and provides proposals for improving its efficiency in the future.